Married Women In Industry (Relations industrielles / Industrial Relations, 1954)
The article reviews the booklet, "Married Women In Industry," by E.M. Harris. Published by the Institute of Peronnel Management, London. Occasional Papers, No. 4 (30 pages). 1954.